Potensi Ekstrak Rimpang Kunyit Sebagai Prebiotik Pemacu Pertumbuhan Lactobacillus plantarum Secara In Vitro - MIN RAHMINIWATI; SAEPUDIN RAHMATULLAH; IRMANIDA BATUBARA; SUMINAR S. ACHMADI (JURNAL ILMU KEFARMASIAN INDONESIA, 2014)
Turmeric contains curcumin which has antibacterial and anti-inflammatory activities. In addition, turmeric contain also carbohydrates that has potency as a prebiotic agent. Research on turmeric extract that was obtained by maceration in variety of solvent, temperatures and time have been carried out to get the most potent prebiotic extract of turmeric to stimulate L. plantarum growth. Maceration with water at 28oC for 1 hour resulted in extract which can enhance the growth of L. plantarum approximately is higher than controls at a concentration of 1 ppm. L. plantarum growth rate increases with increasing concentration of extract. Sugars content of oligosaccharide in the extract were stakiosa, sucrose and lactose of 3014, 164, and 82 ppm respectively. It is concluded that oligosaccharide in turmeric extract is potential as prebiotic agent to increase L. plantarum growth.